(untitled) (American Journal of Islam and Society, 1992)
This essay will attempt to propose a methodology for the study of the history of Islamic science. The method outlined below offers a way of reinterpreting the history of Islamic science and covers those angles that have been obscured by the method of narrative writing. The project itself remains an immense one and cannot be simply dismissed, as there is always room for reinterpretation. Foucault writes: “History shows that everything that has been thought of will be thought of again by a thought that does not yet existl’l There is no value in the glorification of the past if that glorification hides the conflict within the tradition-a conflict that may remain unresolved. The central focus of this study will be that of the externalist method rather than the intemalist method. To the internalist, the methodology of science follows a rational course: to theexternalist, many irrational factors, at times beyond the rational, may influence the direction of science. However, one must state, with caution, that both methods are indispensable, for the development of science can only be understood with a clear insight into how they intersect in the evolution of science as a body of knowledge. Besides presenting an evolution of scientific ideas, they give an insight into scientific research itself and, secondly, into the sociological context in which science developed. This is only possible, Kuhn states, if there is a bridge between internal history (which concerns itself with the evolution of the field, its chief actors, and in what way their discoveries and methods have helped to develop the field [this view is insular as it argues that ...